Observations of binary stars with the differential speckle survey instrument. III. measures below the diffraction limit of the WIYN telescope - Horch, Elliott P.; van Altena, William F.; Howell, Steve B.; Sherry, William Henry; Ciardi, David R. (The Astronomical Journal, 2011)
In this paper, we study the ability of CCD- and electron-multiplying-CCD- based speckle imaging to obtain reliable astrometry and photometry of binary stars below the diffraction limit of the WIYN 3.5 m Telescope. We present a total of 120 measures of binary stars, 75 of which are below the diffraction limit. The measures are divided into two groups that have different measurement accuracy and precision. The first group is composed of standard speckle observations, that is, a sequence of speckle images taken in a single filter, while the second group consists of paired observations where the two observations are taken on the same observing run and in different filters. The more recent paired observations were taken simultaneously with the Differential Speckle Survey Instrument, which is a two-channel speckle imaging system. In comparing our results to the ephemeris positions of binaries with known orbits, we find that paired observations provide the opportunity to identify cases of systematic error in separation below the diffraction limit and after removing these from consideration, we obtain a linear measurement uncertainty of 3-4 mas. However, if observations are unpaired or if two observations taken in the same filter are paired, it becomes harder to identify cases of systematic error, presumably because the largest source of this error is residual atmospheric dispersion, which is color dependent. When observations are unpaired, we find that it is unwise to report separations below approximately 20 mas, as these are most susceptible to this effect. Using the final results obtained, we are able to update two older orbits in the literature and present preliminary orbits for three systems that were discovered by Hipparcos. © 2011. The American Astronomical Society. All rights reserved..
Keywords: binaries: visual; dept.phy; peer-reviewed; techniques: high angular resolution; techniques: interferometric; techniques: photometric

The WIYN Speckle Survey: Toward the Thin and Thick Disk Binary Populations - Horch, Elliott P.; van Altena, William F.; Docobo, J. A.; Tamazian, V. S.; Balega, Y. Y. (INTERNATIONAL WORKSHOP ON DOUBLE AND MULTIPLE STARS: DYNAMICS, PHYSICS, AND INSTRUMENTATION, 2011)
The WIYN Observatory speckle program has been in operation since 1997, taking data mainly with a large-format, low-noise CCD detector. However, new instrumentation, first used in 2008, has created the possibility to use two detectors simultaneously, collecting light in two different filters. The program also now has access to two electron-multiplying CCD cameras, which dramatically improve the limiting magnitude of the diffraction-limited imaging capabilities. The application of this instrumentation to an ongoing survey of the Hipparcos Double Stars and other projects is discussed. © 2011 American Institute of Physics.
Keywords: binaries: visual; dept.phy; stars: stellar populations; techniques: high angular resolution; techniques: interferometric; techniques: photometric

Observations of Binary Stars with the Differential Speckle Survey Instrument. II. Hipparcos Stars Observed in 2010 January and June - Horch, Elliott P.; Gomez, Shamilia C.; Sherry, William Henry; Howell, Steve B.; Ciardi, David R.; Anderson, Lisa M.; van Altena, William F. (The Astronomical Journal, 2011)
The results of 497 speckle observations of Hipparcos stars and selected other targets are presented. Of these, 367 were resolved into components and 130 were unresolved. The data were obtained using the Differential Speckle Survey Instrument at the WIYN 3.5 m Telescope. (The WIYN Observatory is a joint facility of the University of Wisconsin-Madison, Indiana University, YaleUniversity, and theNational Optical AstronomyObservatories.) Since the first paper in this series, the instrument has been upgraded so that it now uses two electron-multiplying CCD cameras. The measurement precision obtained when comparing to ephemeris positions of binaries with very well known orbits is approximately 1-2 mas in separation and better than 0.̊ 6 in position angle. Differential photometry is found to be in very good agreement with Hipparcos measures in cases where the comparison is most relevant. We derive preliminary orbits for two systems. © 2011. The American Astronomical Society.
Keywords: Binaries: Visual; Techniques: High angular resolution; Techniques: Interferometric; Techniques: Photometric; dept.phy; peer-reviewed

Speckle Observations of Binary Stars with the Wiyn Telescope. Vii. Measures During 2008-2009 - Horch, Elliott P.; Bahi, Lizzie Anne P.; Gaulin, Joseph R.; Howell, Steve B.; Sherry, William Henry; Gallé, Roberto Baena; van Altena, William F. (The Astronomical Journal, 2011)
Five hundred thirty-one speckle measures of binary stars are reported. These data were taken mainly during the period 2008 June through 2009 October at the WIYN 3.5m Telescope at Kitt Peak and represent the last data set of single-filter speckle observations taken in the WIYN speckle program prior to the use of the current two-channel speckle camera. The astrometric and photometric precision of these observations is consistent with previous papers in this series: we obtain a typical linear measurement uncertainty of approximately 2.5mas, and the magnitude differences reported have typical uncertainties in the range of 0.1-0.14 mag. In combination with measures already in the literature, the data presented here permit the revision of the orbit of A 1634AB (= HIP 76041) and the first determination of visual orbital elements for HDS 1895 (= HIP 65982).
Keywords: binaries: visual; dept.phy; peer-reviewed; techniques: high angular resolution; techniques: interferometric; techniques: photometric

In-situ Star Formation in the Outskirts of the Large Magellanic Cloud: Gaia DR2 Confirmation. - Casetti-Dinescu, Dana I; Girard, Terrence M; Bidin, Christian Moni; Zhang, Lan; Mendez, Rene A; Vieira, Katherine; Korchagin, Vladimir I; van Altena, William F (The Astrophysical journal, 2018)
We explore the Gaia data release 2 (DR2) proper motions of six young, main-sequence stars, members of the Large Magellanic Cloud (LMC) reported by Moni Bidin et al. These stars are located in the outskirts of the disk, between 7degree and 13degree from the LMC's center where there is very low H I content. Gaia DR2 proper motions confirm that four stars formed locally, in situ, while two are consistent with being expelled via dynamical interactions from inner, more gas-rich regions of the LMC. This finding establishes that recent star formation occurred in the periphery of the LMC, where thus far only old populations were known.
Keywords: Magellanic Clouds; dept.phy; stars: early-type; stars: kinematics and dynamics

Chemical composition of young stars in the leading arm of the Magellanic system - Zhang, Lan; Moni Bidin, Christian; Casetti-Dinescu, Dana I.; Méndez, Réne A.; Girard, Terrence M.; Korchagin, Vladimir I.; Vieira, Katherine; van Altena, William F.; Zhao, Gang (The Astrophysical Journal, 2017)
Chemical abundances of eight O- and B-type stars are determined from high-resolution spectra obtained with the MIKE instrument on the Magellan 6.5 m Clay telescope. The sample is selected from 42 candidates for membership in the Leading Arm (LA) of the Magellanic System. Stellar parameters are measured by two independent grids of model atmospheres and analysis procedures, confirming the consistency of the stellar parameter results. Abundances of seven elements (He, C, N, O, Mg, Si, and S) are determined for the stars, as are their radial velocities and estimates of distances and ages. Among the seven B-type stars analyzed, the five that have radial velocities compatible with membership of the LA have an average [Mg/H] of -0.42 ±0.16, significantly lower than the average of the remaining two, [Mg/H] = -0.07 ±0.06, which are kinematical members of the Galactic disk. Among the five LA members, four have individual [Mg/H] abundance compatible with that in the LMC. Within errors, we cannot exclude the possibility that one of these stars has an [Mg/H] consistent with the more metal-poor, SMC-like material. The remaining fifth star has an [Mg/H] close to Milky Way values. Distances to the LA members indicate that they are at the edge of the Galactic disk, while ages are of the order of ∼50-70 Myr, lower than the dynamical age of the LA, suggesting a single star-forming episode in the LA. V LSR of the LA members decreases with decreasing Magellanic longitude, confirming the results of previous LA gas studies. © 2017. The American Astronomical Society. All rights reserved..
Keywords: dept.phy

The Origins of Young Stars in the Direction of the Leading Arm of the Magellanic Stream: Abundances, Kinematics, and Orbits. - Zhang, Lan; Casetti-Dinescu, Dana I; Bidin, Christian Moni; Mendez, Rene A; Girard, Terrence M; Vieira, Katherine; Korchagin, Vladimir I; van Altena, William F; Zhao, Gang (The Astrophysical journal, 2019)
We explore the origins of the young B-type stars found by Casetti-Dinescu et al. (2014) at the outskirts of the Milky-Way disk in the sky region of Leading Arm of the Magellanic Stream. High-resolution spectroscopic observations made with the MIKE instrument on the Magellan Clay 6.5m telescope for nine stars are added to the previous sample analyzed by Zhang et al. (2017). We compile a sample of fifteen young stars with well-determined stellar types, ages, abundances and kinematics. With proper motions from Gaia DR2 we also derive orbits in a realistic Milky-Way potential. We find that our previous radial-velocity selected LA candidates have substantial orbital angular momentum. The substantial amount of rotational component for these stars is in contrast with the near-polar Magellanic orbit, thus rendering these stars unlikely members of the LA. There are four large orbital-energy stars in our sample. The highest orbital-energy one has an age shorter than the time to disk crossing, with a birthplace z = 2.5 kpc and R GC ~ 28 kpc. Therefore, the origin of this star is uncertain. The remaining three stars have disk runaway origin with birthplaces between 12 and 25 kpc from the Galactic center. Also, the most energetic stars are more metal poor ([Mg/H] =-0.50 +/- 0.07) and with larger He scatter (sigma [He/H] = 0.72) than the inner disk ones ([Mg/H] = 0.12 +/- 0.36, sigma [He/H] = 0.15). While the former group's abundance is compatible with that of the Large Magellanic Cloud, it could also reflect the metallicity gradient of the MW disk and their runaway status via different runaway mechanisms.
Keywords: dept.phy; stars: abundances; stars: early-type; stars: kinematics and dynamics